Chaplaincy, Spiritual Care and Moral Injury: Considerations Regarding Screening and Treatment - Carey, Lindsay B.; Hodgson, Timothy J. (Frontiers in Psychiatry, 2018)
Moral injury is a complex trauma related syndrome involving a correlation of biological, psychological, social and spiritual symptoms that can have substantial impact upon health and well-being. This paper argues for a holistic bio-psycho-social-spiritual approach to moral injury, by including chaplaincy in the screening and treatment of moral injury among actively serving military members and retired veterans. As part of the moral injury treatment process, and in alignment with the World Health Organisation’s Spiritual Intervention Codings, a new technique is proposed, ‘Pastoral Narrative Disclosure’ (PND), as a guide for chaplains and others trained in spiritual care to assist those suffering from moral injury.